2018
DOI: 10.1002/jso.25118
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction with constrained scapular prosthesis after total scapulectomy for scapular malignant tumor

Abstract: Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…At the nal mean follow-up of 61.8 months, the mean MSTS score was 23.5. There were no cases of dislocation or loose joints [20].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At the nal mean follow-up of 61.8 months, the mean MSTS score was 23.5. There were no cases of dislocation or loose joints [20].…”
Section: Discussionmentioning
confidence: 88%
“…At latest follow-up, there was one case of dislocation, one case of infection and the average MSTS score was 76.7% [19]. Wang B et al (2018) reported a series of 8 cases treated with total scapular replacement with a constrained reverse shoulder prosthesis after malignant tumor resection. At the nal mean follow-up of 61.8 months, the mean MSTS score was 23.5.…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, Eckardt [ 18 ] made the first attempt to perform prosthetic reconstruction after total scapulectomy. Since then, several studies have reported that prosthetic reconstruction can achieve good oncological and functional outcomes [ 8 , 19 , 20 ]. Li [ 21 ] reported 17 cases of scapular malignant tumors undergoing total scapulectomy and reconstruction with prostheses.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 A constrained endoprosthesis may lower the complication rate and results in variable function. 13 , 14 …”
Section: Scapulamentioning
confidence: 99%
“…11,12 A constrained endoprosthesis may lower the complication rate and results in variable function. 13,14 The glenoid fragment can be secured to the clavicle to offer a stable platform for elevation (Fig. 1c).…”
Section: Scapulamentioning
confidence: 99%